2020
DOI: 10.1044/2020_jslhr-19-00188
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Lagged Analysis of Emotion Regulation, Peer Problems, and Emotional Problems in Children With and Without Early Language Difficulties: Evidence From the Millennium Cohort Study

Abstract: Purpose Adolescents with a history of language difficulties are at risk for increased social and emotional difficulties; however, the pathways involved are unclear. We examine the contribution of poor emotion regulation by comparing longitudinal data from children at risk of developmental language disorder (rDLD) and the general population. Method Data from the Millennium Cohort Study were analyzed at ages 3, 5, 7, 11, and 14 years. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…FEEL-KJ: Vragenlijst over emotieregulatie bij kinderen en jongeren [Questionnaire to Assess Children's and Adolescents Emotion Regulation Strategies Grob and Smolenski, 2005; Dutch version by Braet et al, 2014] is an instrument whose purpose is to measure emotional regulation in different emotions. In addition, the FEEL-KJ measures both internal and external regulation strategies.…”
Section: Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations
“…FEEL-KJ: Vragenlijst over emotieregulatie bij kinderen en jongeren [Questionnaire to Assess Children's and Adolescents Emotion Regulation Strategies Grob and Smolenski, 2005; Dutch version by Braet et al, 2014] is an instrument whose purpose is to measure emotional regulation in different emotions. In addition, the FEEL-KJ measures both internal and external regulation strategies.…”
Section: Instrumentsmentioning
confidence: 99%
“…The FEEL-KJ in its Dutch version has adequate psychometric properties, with an internal consistency (Cronbach's alpha) of the 15 scales ranging from a α = 0.59 to a α = 0.91. For the secondary scales, α = 0.94 (8-12) and α = 0.95 (13-18) for adaptive strategies; α = 0.89 (8-12) and α = 0.92 for maladaptive strategies and α = 0.79 (8-12) and α = 0.89 (13-18) for external strategies (Braet et al, 2014). The internal consistency index (i.e.…”
Section: Maladaptive Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents with low language (LL) ability also present with impairment(s) in language, but not to the degree necessary to warrant a diagnosis of DLD. In addition, adolescents with DLD and those with LL can have pervasive needs in non-language domains such as psychosocial functioning (Conti-Ramsden et al, 2013;Yew and O'Kearney, 2013;Forrest et al, 2020;Toseeb and St Clair, 2020) and emotional regulation skill (Fujiki et al, 2002) and report lower self-perceived health than their TD peers (Beitchman et al, 2014). Given such challenges it is likely that individuals with DLD would be at increased risk of poorer wellbeing than their TD peers.…”
Section: Levels Of Wellbeing In Developmental Language Disordermentioning
confidence: 99%
“…A number of studies have found that children with DLD when aged 4-7 years are at increased risk of later mental health difficulties when aged 8-19 years, compared with their typically-developing peers (Conti-Ramsden & Botting, 2008;Wadman, Botting, Durkin & Conti-Ramsden, 2011;Conti-Ramsden, Mok, Pickles & Durkin, 2013;Beitchman et al, 2001; although see Snowling, Bishop, Stothard, Chipchase & Kaplan, 2006;Redmond & Rice, 2002 for counterevidence). These findings are hard to interpret since, despite group differences, continuous measures of language ability do not always predict internalizing symptoms in the children studied (Conti-Ramsden & Botting, 2008;Wadman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%